Retention of robot-assisted surgical skills in urological surgeons acquired using Mimic dV-Trainer - Teishima, Jun; Hattori, Minoru; Inoue, Shogo; Hieda, Keisuke; Ohara, Shinya; Egi, Hiroyuki; Ohdan, Hideki; Matsubara, Akio (Canadian Urological Association Journal, 2014)
Introduction: We assess the retention of robot-assisted surgical skills among urologic surgeons. Methods: The robot-assisted surgery skills of 20 urologic surgeons were assessed using a Mimic dV-Trainer program (Mimic Technologies, Inc., Seattle, WA) consisting of 6 tasks. These 20 surgeons had no previous experience either using the Mimic dV-Trainer or acting as the main surgeon in robot-assisted surgery. The surgeons completed the program 4 times in a row; after 1 year, they completed it again for a fifth time. Performance scores were recorded using the Mimic dV-Trainer’s built-in algorithm. Results: For all 6 tasks, there were significant improvements to the scores in the fourth trials compared with those in the first trials. The scores in the fifth trials did not significantly decline compared with those in the fourth trials. There was no significant difference between the fifth trial scores of surgeons with laparoscopic surgery skills/experience and those without. Conclusion: Our results indicate that fundamental robot-assisted surgical skills can be retained in the long-term after they are acquired.